Influence of early fluid overload on bronchopulmonary dysplasia in very low-birth-weight infants - Li, Yu-Jie; Zhu, Xiao-Fang; Liu, Jian-Hong; Yi, Xiao-Qian; He, Hao (Frontiers in Pediatrics, 2022)
Objective: This study aimed to determine the influence of fluid overload on bronchopulmonary dysplasia (BPD) in very low-birth-weight infants (VLBWI) within 1 week after birth. Methods: This was a retrospective case control study conducted in the Jingzhou Central Hospital. The clinical data of VLBWI (with a birth weight [BW] < 1,500g and 26 weeks ≤ gestational age [GA] < 32 weeks) who were admitted to the neonatal intensive care unit of this hospital from January 2016 to December 2021 were analyzed retrospectively. A total of 157 cases were enrolled and divided into a BPD group (n = 60) and a non-BPD group (n = 97) according to whether BPD was present. The general condition, fluid intake, and fluid overload of the two groups of neonates within 1 week after birth were compared. The logistic regression was used to assess the association between infant characteristics and BPD. The ROC curve was used to assess how well the 7 day cumulative fluid overload predicted BPD, and to identify an optimal cut off for prediction. Results: The comparison of the patients’ general condition revealed that the neonates in the BPD group had a younger GA, lower BW, lower 5-minute Apgar score, longer duration of invasive mechanical ventilation, and higher incidence of intrauterine infections and administration of surfactants (P< 0.05). The differences in the other indicators were not statistically significant between the two groups. The logistic regression analysis revealed that a younger GA, the presence of intrauterine infection, and a 7-day cumulative fluid overload were the risk factors for the development of BPD. A ROC curve was plotted with the 7-day cumulative fluid overload as the test variable and BPD as the status variable. The area under the curve was 0.75 (95% confidence interval: 0.664–0.826, P = 0.042), with a sensitivity of 76.7% and a specificity of 70.1%, corresponding to a 7-day cumulative fluid overload of 36.2%. Conclusion:A younger GA, the presence of intrauterine infection, and a 7-day cumulative fluid overload were risk factors for the development of BPD. A 7 day cumulative fluid overload threshold of 36.2% best predicted the development of BPD.